PENGARUH STRUKTUR KEPEMILIKAN, PERTUMBUHAN PERUSAHAAN, DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP PENERIMAAN OPINI GOING CONCERN - Salsabila Katarin Puspamarta; Siti Mundiroh (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
This study aims to prove empirically the effect of ownership structure, company’s growth, and opinion prior year on the acceptance of going concern opinion. This research was conducted on basic materials sector listed on Indonesia Stock Exchange from 2017-2021 period. Data used is logistic regression. The sample selection was carried out using the purposive sampling method from secondary data in the form a financial statements and found as many as 16 sample companies with a total of 5 years of observations, so the total sample in this study was 80 observational data. Based on the test results, it was found that ownership structure, company’s growth, and opinion prior year have a simultaneous effect of opinion year on acceptance of going concern opinion. Partially, this study proves the influence of opinion prior year on acceptance of going concern opinion. Meanwhile, institusional ownership, managerial ownership, and company’s growth partially have no effect on the acceptance of going concern opinion.